1978
DOI: 10.1099/00221287-108-2-283
|View full text |Cite
|
Sign up to set email alerts
|

An Electron Microscopic Study of the Location of Peptidoglycan in Group A and C Streptococcal Cell Walls

Abstract: The morphological appearance of deproteinized Group A and C streptococcal walls after treatment by different procedures extracting teichoic acids and polysaccharides (formamide, hydrochloric acid, nitrous acid, trichloroacetic acid, sulphuric acid, sodium hydroxide and sodium deoxycholate) was compared with the content of teichoic acids and polysaccharides remaining in the treated walls. All procedures extracted teichoic acids almost completely, but polysaccharides were extracted to various degrees. The ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Under these conditions, the walls did not show a trilamellar structure, whereas this structure was regained together with wall teichoic acid on transfer to the permissive temperature. On the other hand, extraction of the walls of group A and group C streptococci with various reagents which removed from 20 to 95% of the rhamnose present did not alter the trilamellar appearance, although there were considerable reductions in thickness (169). Similar results were obtained with walls of S. faecalis (68,165) and L. arabinosus (13), from which the secondary polymers were extracted with trichloroacetic acid.…”
Section: Wall Teichoic Acidssupporting
confidence: 53%
“…Under these conditions, the walls did not show a trilamellar structure, whereas this structure was regained together with wall teichoic acid on transfer to the permissive temperature. On the other hand, extraction of the walls of group A and group C streptococci with various reagents which removed from 20 to 95% of the rhamnose present did not alter the trilamellar appearance, although there were considerable reductions in thickness (169). Similar results were obtained with walls of S. faecalis (68,165) and L. arabinosus (13), from which the secondary polymers were extracted with trichloroacetic acid.…”
Section: Wall Teichoic Acidssupporting
confidence: 53%
“…Identical results were obtained with choline-containing and choline-free cell walls examined with rabbit anti-C-Ps antiserum. Because this antiserum is known to react with peptidoglycan fragments (17,25), the experiments were repeated with monoclonal antibody specific for the phosphoryl-choline part of the C-Ps (16). In agreement with the previous results the monoclonal antibody bound to both sides of choline-containing cell walls but, as expected, not to the choline-free cell walls.…”
Section: Discussionmentioning
confidence: 99%
“…The RhaCWP is a major component in streptococcal species comprising about 40%–60% of the cell wall by weight (McCarty 1952 ; Krause and McCarty 1962a ; Krause 1963 ; Doran and Mattingly 1982 ). Correspondingly, cell wall thickness is visually reduced by 40%–50% after chemical extraction of the Group-specific carbohydrate (Swanson and Gotschlich 1973 ; Wagner and Wagner 1978 ). Recent mutagenesis studies confirmed the structural importance of streptococcal group antigens; complete loss of RhaCWP expression resulted in severe growth and cell division abnormalities (Fig.…”
Section: Introductionmentioning
confidence: 99%